Facilitation and Teacher Behaviors: An Analysis of Literacy Teachers' Video-Case Discussions. (March 2014) - Arya, Poonam; Christ, Tanya; Chiu, Ming Ming
This study explored how peer and professor facilitations are related to teachers' behaviors during video-case discussions. Fourteen inservice teachers produced 1, 787 turns of conversation during 12 video-case discussions that were video-recorded, transcribed, coded, and analyzed with statistical discourse analysis. Professor facilitations (sharing experiences; affirming ideas; and asking for critical thinking, information, observations, and connections) and peer facilitations (recall, critical thinking, connections, and affirmations) in recent conversation turns were linked to teachers' current turn behaviors, including recalling information, critical thinking, and making connections to content in video cases. These results suggest that modeling, scaffolding, and co-construction among professors and peers support specific teacher behaviors during video-case discussions.